Anxiety, stress and daily social media usage in predicting social media addiction: a sample of vocational school - Bilge, Yıldız; Baydili, Kürşad Nuri; Göktaş, Seyyide Şifa (Journal of Dependence, 2020)
Objective: The aim of the study is to determine the relationship between depression, anxiety and stress symptoms and social media addiction and the level of predicting social media addiction.Method: The sample of the study consisted of a total of 281 people (208 female, 73 male) studying at a state university, Vocational School of Health. Demographic Information Form, Social Media Addiction Scale-Adult Form (SAS-AF) and Depression Anxiety Stress Scale (DASS) were applied to participants.Results: When demographic information and social media addiction Scale scores were compared, it was found that there was no difference in terms of other variables except daily social media use. According to used of social media applications, the participant susing Instagram application showed a significant difference in addiction scores than other social media users. As a result of the regression analysis, respectively, associated with anxiety, daily social media use and stress levels were effective, it was specified that these three variables were predicted as social media addiction scores by 32.6%.Conclusion: Social media addiction and depression, anxiety and stress variables were related to each other and anxiety, stress and daily social media use were effective variables in explaining social media addiction scores.
Keywords: Social media addiction; depression; anxiety; stress; use of daily social media